The Impact of The Boss Baby 2 Animated Film on Children’s Personality and Behavior - Tawakkal, Afifah Ibna Fatina; Mariana, Ana; Mukhsin, Hasna Nurain (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
This research aims to find out the impact of The Boss Baby 2 Animated Film on Children’s Personality and Behavior. This research uses descriptive qualitative method and Sigmund Freud's theory to analyze the impact of watching animated films on various aspects of children's personality and behavior focusing on the Id, Ego, and superego. The researcher found that The Boss Baby 2 is about adult issues framed from the children's perspective and id are too dominant in this animated film so it is recommended children watching this film with adults. The researcher hope, that readers can develop a better understanding of psychoanalysis study through this research and hope can be an additional reference in studying psychoanalysis for further researcher.Keywords: Freud’s theory, id, ego, superego